2022
DOI: 10.37934/arfmts.97.2.17
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature Effect of Madeira Vine (Anredera Cordifolia) Leaf Oil Extraction and Its Characterization as An Additive in Health Supplement Product

Abstract: The immune system is one of the most important things that need to be preserved in the midst of the Corona Virus Disease 2019 (Covid-19) pandemic. Consuming the components of the compounds contained in Madeira vine (Binahong) leaf oil in the right and regular doses can be one way to enhance the immune system. This oil can be obtained by carrying out the extraction process with the reflux method on Madeira vine leaf. This study aimed to determine the optimal time and temperature of Madeira vine leaf oil extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The instrument consists of an electronic unit separated from the stainless-steel measuring unit. A sample volume of 0.3 ml is sufficient for measuring process [7,9]. The refractometer is equipped with a Peltier thermostat allowing measurement of refractive index at any selected temperature up to 80 °C.…”
Section: Refractive Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument consists of an electronic unit separated from the stainless-steel measuring unit. A sample volume of 0.3 ml is sufficient for measuring process [7,9]. The refractometer is equipped with a Peltier thermostat allowing measurement of refractive index at any selected temperature up to 80 °C.…”
Section: Refractive Indexmentioning
confidence: 99%
“…This is because the selling price of ethanol as a beverage is higher than that of ethanol as a solvent. In addition to the type of solvent, another influential factor is time, where a short time during extraction will produce a small yield and a long time will consume a lot of energy, so the extraction will not be effective [7]. Therefore, research continues to identify other types of alcohols that have a lower risk of deviation.…”
Section: Introductionmentioning
confidence: 99%
“…The amino compound also shows antimicrobial activity [25]. Phytol components can stimulate insulin secretion by pancreatic cells and lower blood glucose, so it can be concluded that binahong leaf oil is also antiglycemic [26].…”
Section: Gcms or Gas Chromatography-mass Spectrophotometry Analysismentioning
confidence: 99%